Gender, Bullying Victimization, Depressive Symptoms, and Suicidality - Strohacker, Emily (International journal of offender therapy and comparative criminology, 2021)
Bullying victimization can have serious consequences for adolescents. This article examines the association between traditional and cyberbullying victimization, depressive symptoms, and suicidality in a national school-based sample, utilizing general strain theory (GST) as a guide to how these variables might relate to each other. We additionally examine whether the associations between these variables differ by gender. Results suggest that traditional and cyberbullying victimization have significant, positive associations with both depressive symptoms and suicidality. Results are partly supportive of the full model suggested by GST, with the associations between bullying and suicidality being weakened in some models when accounting for depressive symptoms. Gender differences also emerge. These findings are discussed in relation to their relevance for policy and theory.